2020
DOI: 10.1080/17453674.2020.1854502
|View full text |Cite
|
Sign up to set email alerts
|

Most surgeons still prefer to reduce overriding distal radius fractures in children

Abstract: Background and purpose — Traditionally, overriding distal radius fractures in children have been reduced and immobilized with a cast or treated with percutaneous pin fixation. There is recent evidence that these fractures heal well if immobilized in the bayonet position without reduction. We evaluated the present treatment of these fractures. Methods — A questionnaire including AP and lateral radiographs of overriding distal radius fractures in 3 pre-pubertal children was answered by 213 surgeons fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…However, a recent survey suggested that most European and American surgeons still prefer to reduce these fractures, even in prepubescent children 22 . Furthermore, treatment and follow-up protocols seem to vary substantially 22 . We found a substantial variation in treatment decisions made by individual surgeons in our hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent survey suggested that most European and American surgeons still prefer to reduce these fractures, even in prepubescent children 22 . Furthermore, treatment and follow-up protocols seem to vary substantially 22 . We found a substantial variation in treatment decisions made by individual surgeons in our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this traditional thinking, Crawford et al 20 reported good outcomes in patients <11 years old with completely displaced overriding distal metaphyseal radial fractures immobilized in an overriding position without reduction. In recent surveys, most surgeons still prefer reduction 21,22 . Quality standards for treatment of these fractures have not yet been established.…”
mentioning
confidence: 99%
“…This is not surprising, as the most common fracture type was a simple stable torus fracture. Casting only is considered a less favorable option for complete fractures, since it is thought to be insufficient [ 1 , 3 , 10 , 16 , 17 ] and carries a greater risk of redislocation and other complications, such as malunion [ 1 , 3 , 17 ]. It has been reported that adequate reduction before casting is crucial to prevent redislocation [ 6 , 12 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind this meta-analysis was that there is a significant lack of agreement on the indications of cast type application regarding the treatment of displaced distal forearm fractures in pediatric patients. [26][27][28][29] In a survey, Laaksonen et al 27 reported possible overtreatment and practice variation for treatment of completely displaced distal radius fractures in pediatric patients. In this survey, the majority of surgeons (84% of 213 participating surgeons) chose an AEC to immobilize distal forearm fractures, although earlier reports showed that AEC does not retain the alignment of displaced distal forearm fractures in children any better than BEC.…”
Section: Discussionmentioning
confidence: 99%